Visual feedback adaptation enhances arm-posture coordination during floor-surface perturbations - Tomita, Yosuke; Mani, Hiroki; Hasegawa, Naoya (Frontiers in Human Neuroscience, 2025)
BackgroundMaintaining postural stability during perturbations requires coordinated sensorimotor and interjoint coordination. This study investigated the effects of different feedback modalities (knowledge of results [KR] and continuous visual feedback) on postural adaptation during floor surface perturbations while standing.MethodsNineteen healthy young adults (mean age: 23.1 ± 1.2 years; 12 males) performed an arm-holding task while standing on a backward-translating force platform under five phases: baseline test, KR adaptation training, post-KR adaptation (P-KRA) test, visual adaptation training, and post-visual adaptation (P-VA) test. Endpoint position variability, center of pressure (COP), center of mass (COM), margin of stability (MOS), and interjoint coordination were compared among Baseline, P-KRA, and P-VA using a mixed-model repeated-measures analysis of variance.ResultsCompared to Baseline, endpoint position variability was significantly reduced in the P-VA at both perturbation offset (8.97 ± 1.04 mm vs. 15.35 ± 1.52 mm, p = 0.006) and 1.5 s after offset (14.39 ± 1.02 mm vs. 19.73 ± 1.71 mm, p = 0.027). The MOS at 1.5 s after offset was lower in P-VA (39.33 ± 4.28 mm) than in Baseline (58.04 ± 4.53 mm, p = 0.011), and the minimum MOS was significantly smaller in P-VA (32.20 ± 4.38 mm vs. 50.59 ± 4.26 mm, p = 0.011). Anticipatory COP displacement at onset in P-VA was significantly increased (14.11 ± 1.46 mm vs. 6.20 ± 0.89 mm, p < 0.001) and reduced peak forward COP displacement (89.42 ± 2.00 mm vs. 110.18 ± 3.35 mm, p < 0.001). The time to stability was shorter in P-VA (1,266.42 ± 68.29 ms) than in Baseline (1,525.78 ± 66.11 ms, p = 0.017). The cross-correlation coefficient between the elbow and ankle joints was significantly higher in P-VA than in Baseline (0.98 ± 0.01 vs. 0.89 ± 0.04, p = 0.014).ConclusionThese findings demonstrate that continuous visual feedback adaptation may enhance arm-posture coordination during external perturbations in healthy young adults.